2022
DOI: 10.1055/s-0042-1742411
|View full text |Cite
|
Sign up to set email alerts
|

Could Aspirin Treatment Modify the Assessment of the Uterine Arteries?

Abstract: Objective To analyze whether acetylsalicylic (ASA) intake modifies the mean uterine arteries pulsatility index (UtA-PI) at the 2nd or 3rd trimester in a cohort of pregnant women with abnormal mean UtA-PI at between 11 and 14 weeks of gestation. Methods This is a retrospective cohort study. Singleton pregnancies with abnormal mean UtA-PI at between 11 and 14 weeks of gestation were studied. The participants were divided into 3 groups: 1) If the participant did not take ASA during pregnancy; 2) If the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(78 reference statements)
1
1
0
Order By: Relevance
“…Whilst no effects of aspirin on MAP were observed, aspirin initiated in the first trimester led to a more pronounced decrease in UtA resistance before 20 weeks of gestation compared with placebo. This finding is in line with those of two previous smaller studies 8,29 . Conversely, a previous RCT of 150 mg aspirin vs placebo including 155 participants with UtA-PI > 95 th percentile at 11-14 weeks published before the ASPRE trial showed no significant changes in UtA-PI at 28 weeks of gestation 30 .…”
Section: Interpretation and Clinical Implicationssupporting
confidence: 94%
“…Whilst no effects of aspirin on MAP were observed, aspirin initiated in the first trimester led to a more pronounced decrease in UtA resistance before 20 weeks of gestation compared with placebo. This finding is in line with those of two previous smaller studies 8,29 . Conversely, a previous RCT of 150 mg aspirin vs placebo including 155 participants with UtA-PI > 95 th percentile at 11-14 weeks published before the ASPRE trial showed no significant changes in UtA-PI at 28 weeks of gestation 30 .…”
Section: Interpretation and Clinical Implicationssupporting
confidence: 94%
“…Because of that, there is the hypothesis that women who have high risk of PE perhaps did not develop it because they took ASA during pregnancy. This treatment could have changed the outcome findings, so the conclusions must be very careful when outcomes are measured; perhaps final outcomes had been more serious if this prophylactic treatment would not have ordered at the beginning of the pregnancy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%